Body change techniques in Iranian adolescents: relationship to sex and body weight status - Hatami, Monireh; Mohd Taib, Mohd Nasir; Jamaluddin, Rosita; Abu Saad, Hazizi; Djazayery, Abolghasem (Elsevier, 2013)
Objective: Several studies indicated that techniques to change body weight and appearance were prevalent and different among adolescents. The aim of the study, therefore, was to assess differences in frequency and type of body change techniques used among adolescents by sex and body weight status. Methods: A sample of 758 adolescents aged 12–18 years were recruited from private and public schools in Tehran. Information about socio-demographic background and body change techniques were collected via a self-administered questionnaire. Results: A high percentage of adolescents used body change techniques frequently to alter their body appearance. Girls changed normal eating pattern significantly (p = 0.007) to lose weight more frequently than boys while boys used this method significantly (p = 0.01) to gain weight more frequently than girls. Overweight/obese adolescents exercised significantly to change muscle size (p = 0.03) and changed normal diet to lose weight (p < 0.001) more frequently than normal weight adolescents. The relation between sex and body weight status with body change techniques (p < 0.0) implied that male and female adolescents especially overweight/obese adolescents were frequently trying to change their body appearance. Conclusion: Significant differences existed in using body change techniques according to sex and body weight status and these should be considered in obesity prevention programs for adolescents.